Chemical constituents and biological activity of Euglena gracilis extracts - Tolivia, Analía Alejandra (2013)
Background: Euglena gracilis is a microalgae with a wide range of nutritional requirements,suggesting the existence of diverse physiological patterns. The aim of this work is to carry out a study about secondary metabolites biosynthesis on two strains of E. gracilis cultured in vitro. Methods: Extracts from a Euglena gracilis (Klebs) commercial strain and a wild type isolated from an urban polluted river (MAT) were screened for preliminary identification of chemical constituents. Both strains were studied in their photosynthetic and bleached forms, on their exponential and stationary growth phases. Chromatographic analysis of pigments, lipids, and flavonoids were performed. Besides antioxidant, growth inhibition, and toxic activity were tested in vitro. Results: The phytochemical analysis of extracts indicated the presence of steroids in all samples, cardenolids and triterpenes in the exponential growth phase. With the exception of the photosynthetic MAT strain, tannins were present in all the other on exponential phase samples and flavonoids were only observed in the stationary phase of both photosynthetic strains. Chromatographic profiles show that chlorophyll content decreased while carotenoids content increased in the stationary phase of both photosynthetic strains, and reveal the presence of flavonols derived from quercetin. In concordance with the presence of polyphenols, the fractions with the highest polarity showed antioxidant activity against DPPH and growth inhibition activity in vitro even in the absence of paramylon, previously reported to have antitumoral properties. Conclusion: This work constitutes the first report about polyphenol production in Euglenoids, which allows us a first assessment of the potential of E. gracilis as a source of bioactive products.